Floor Heave Mechanism and Control Technique of Water‐Rich Soft‐Rock Roadway in Thick Coal Seam - Fulian He; Wenli Zhai; Weixin Liu; Ning Sun; Jiayu Song; Jianlong Zhang; Yanhao Wu (Energy Science & Engineering)
ABSTRACT The severe deformation of the surrounding rock of the coal floor in Shanghaimiao mining area is affecting the safe, efficient production of mine wells in this region. In this study, the heave mechanism and control of the roadway floor were investigated through laboratory experiments, field research, theoretical analysis, numerical simulation, and on‐site testing. The results showed that the main reason for the serious damage to the roadway floor was the low strength of the surrounding rock of the roadway floor, and floor damage was exacerbated by the low support strength, hydraulic effects, and mining impact. A mechanical model of the asymmetric floor heave was established, and it was found that the stability of the roadway floor was positively correlated with the floor rock type, the stress concentration coefficients on the two sides of the roadway, and the burial depth, whereas it was negatively correlated with the cohesive force and internal friction angle of the floor rock mass. Expressions for the upward resultant force R of the roadway floor and the stress concentration coefficients K and K′ on both sides of the roadway were derived. The results of a FLAC3D numerical simulation analysis showed that the stress peak in front of the working face was 36 MPa, with a stress concentration factor of 3.7. After the floor support was reinforced, the floor heave was remarkably reduced, with a maximum value of approximately 600 mm, and the floor deformation became somewhat asymmetric. Finally, a double‐seal floor‐reinforcing “inverted arch” control technique was proposed and tested on‐site. The new system could efficiently and stably support the surrounding rock of the roadway.